Kajian Motivasi Kerja dan Budaya Organisasi Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja (Jurnal Ekonomi dan Manajemen, 2023)
This study aims to analyze the effect of work motivation and organizational culture on job satisfaction and its impact on employee performance at the BMKG Malang Climatology Station. The research method used is quantitative with an explanatory research approach. Data were collected through questionnaires distributed to 37 employees using a census technique. Data analysis was conducted using path analysis with SPSS version 20. The results show that work motivation has a positive and significant effect on job satisfaction (β = 0.386; p = 0.011). Organizational culture also has a positive and significant impact on job satisfaction (β = 0.446; p = 0.004). Both work motivation and organizational culture have a positive effect on employee performance, with coefficients of 0.311 (p = 0.015) and 0.266 (p = 0.042), respectively. Job satisfaction significantly influences employee performance (β = 0.405; p = 0.004). The indirect effect of work motivation and organizational culture on performance through job satisfaction is 15.6% and 18.1%, respectively. In conclusion, enhancing work motivation and organizational culture can improve employee performance both directly and through job satisfaction. Therefore, BMKG is advised to strengthen its motivation system and foster a positive organizational culture to optimize employee satisfaction and performance in the workplace.